Redes sócio-técnicas de governança ambiental em Porto Alegre - Juliane Zeve; Klaus Frey (Ciências Sociais Unisinos)
This article is about urban environmental governance in the city of Porto Alegre, in accordance with the virtual representation of the relationship network among the actors involved in local environmental politics. The paper reveals the importance of improved processes of interactive co-operation through new information and communication technologies in order to achieve effective strategies for local sustainable development.